Participation of Acyl-Coenzyme A Synthetase FadD4 of Pseudomonas aeruginosa PAO1 in Acyclic Terpene/Fatty Acid Assimilation and Virulence by Lipid A Modification - Martínez-Alcantar, Lorena; Orozco, Gabriela; Díaz-Pérez, Alma Laura; Villegas, Javier; Reyes-De la Cruz, Homero; García-Pineda, Ernesto; Campos-García, Jesús (Frontiers in Microbiology, 2021)
The pathogenic bacterium Pseudomonas aeruginosa possesses high metabolic versatility, with its effectiveness to cause infections likely due to its well-regulated genetic content. P. aeruginosa PAO1 has at least six fadD paralogous genes, which have been implicated in fatty acid (FA) degradation and pathogenicity. In this study, we used mutagenesis and a functional approach in P. aeruginosa PAO1 to determine the roles of the fadD4 gene in acyclic terpene (AT) and FA assimilation and on pathogenicity. The results indicate that fadD4 encodes a terpenoyl-CoA synthetase utilized for AT and FA assimilation. Additionally, mutations in fadD paralogs led to modification of the quorum-sensing las/rhl systems, as well as the content of virulence factors pyocyanin, biofilm, rhamnolipids, lipopolysaccharides (LPS), and polyhydroxyalkanoates. In a Caenorhabditis elegans in vivo pathogenicity model, culture supernatants from the 24 h grown fadD4 single mutant increased lethality compared to the PAO1 WT strain; however, the double mutants fadD1/fadD2, fadD1/fadD4, fadD2/fadD4, and single mutant fadD2 increased worm survival. Correlation analysis indicated an interaction between worm death by the PAO1 strain, the fadD4 mutation, and the virulence factor LPS. FAME analysis of LPS revealed that proportion of the LPS and FA on lipid A were modified by the fadD4 mutation, suggesting that FadD4 is also involved in the synthesis/degradation and modification of the lipid A component of LPS. LPS isolated from the fadD4 mutant and double mutants fadD1/fadD4 and fadD2/fadD4 showed differential behavior to induce an increase in body temperature in rats injected with LPS compared to the WT strain or from the fadD1 and fadD2 mutants. In agreement, LPS isolated from the fadD4 mutant and double mutants fadD1/fadD2 and fadD2/fadD4 increased the induction of IL-8 in rat sera, but IL1- cytokine levels decreased in the double mutants fadD1/fadD2 and fadD1/fadD4. The results indicate that the fadD genes are implicated in the degree of pathogenicity of P. aeruginosa PAO1 induced by LPS-lipid A, suggesting that FadD4 contributes to the removal of acyl-linked FA from LPS, rendering modification in its immunogenic response associated to Toll-like receptor TLR4. The genetic redundancy of fadD is important for bacterial adaptability and pathogenicity over the host.